A vascular lesion in hip revision arthroplasty: a case report - Giaretta, Stefano; Micheloni, Gian Mario; Mosconi, Federico; Luppi, Valentina; Vanzetti, Alessandro; Gulmini, Marco; Momoli, Alberto (Acta Biomedica Atenei Parmensis, 2021)
Vascular injuries during hip revision surgery can be life-threatening complications for patients. There are many aspects to consider when approaching this type of surgery for an optimal diagnostic and therapeutic strategy, as a careful planning with extensive preoperative investigations, a full attention during the surgical procedure and the use of suitable material for a proper treatment. This kind of surgery can require a dedicated and trained multidisciplinary team. We report a case of an acute intraoperative vascular lesion during an acetabular revision performed in a 55-years-old patient.